Pertumbuhan larva ikan Betok (Anabas Testudineus Bloch) dengan pemberian pakan alami - Agus Budi Prasetya; - Suriansyah; - Rosita; Hendri Bugar (Fakultas Peternakan Universitas Kristen Palangka Raya, 2016)
Feed that best suits the needs of the larvae is a natural feed (plankton), because it fits the mouth opening of larvae. Natural feed is believed to increase the relative growth and survival of larvae, contains highly nutritious and endo-enzym and micro-sized that fit to the larval mouth opening. Natural feed obtained from fertilization carried out in the pool with organic fertilizer (chicken manure) and cabbage leaves. This study aims to determine the growth of Climbing perch fish larvae fed with the natural feed. This study used Completely Randomized Design (CRD) with 4 treatments and 3 replications. The treatments were consisting of A (without water filtering), B (filtering 20 liters of water), C (filtering 30 liters of water), and D (filtering 40 liters of water). The sample in this research was the larvae of the Climbing perch fish (3 days after hatching). The results showed that the giving of natural feed from fertilization provided significant effect on the treatment. Feeding with natural feed from filtering 40 liters of water had more plenty and variety of natural food then other treatments. The relative growth and survival rate of fish larvae were 6.3 % and 87.9 % respectively. Key words : Natural Feed, Climbing perch larvae, growth, survival rate.